Organizational Culture as a Driver of Technology Innovation Management: A Qualitative Review - Muhammad Rizki; Muhammad Luthfi Hamzah (Yayasan Pendidikan Islam Al-Matani, 2025)
Organizational culture has increasingly been recognized as a critical factor in the successful management of technology-driven innovation, particularly in the context of rapid digital transformation. Despite extensive research on innovation and technology adoption, existing studies often address organizational culture, innovation, and digital transformation in a fragmented manner. This study aims to examine the role of organizational culture in technology innovation management through a qualitative literature review. The review analyzes recent and reputable international studies to identify key cultural mechanisms that influence innovation processes and outcomes. Using a qualitative content analysis approach, the selected literature was systematically examined to identify recurring themes related to organizational culture, leadership, digital transformation, and innovation performance. The findings reveal that organizational culture plays a central role in technology innovation management by shaping employee behavior, leadership effectiveness, digital capabilities, and strategic alignment. Innovation is found to frequently mediate the relationship between organizational culture and organizational performance, while digital transformation both depends on and reshapes organizational culture, indicating a reciprocal relationship. Furthermore, cultural resistance, lack of digital mindset, and misalignment of values emerge as major challenges in technology-driven innovation initiatives. This study contributes to the innovation management literature by providing an integrative synthesis that positions organizational culture as a strategic and dynamic capability in technology innovation management. The findings offer theoretical insights and practical implications for organizations seeking to align cultural transformation with technological innovation to achieve sustainable competitive advantage.